Antithrombotic treatment in patients with atrial fibrillation in special clinical conditions - Kukla, Piotr; Czarnecka, Danuta (Przewodnik Lekarza/Guide for GPs, 2008)
Nowadays the treatment of atrial fibrillation (AF) presents 3 main directions: rate control, rhythm control and antithrombotic treatment. For patients with a past history of stroke or transient ischaemic attack (TIA) the annual risk of stroke is 2-4%. About 25% of episodes of stroke in patients older than 80 years are caused by AF. Taking into consideration patients without any risk factors (the low risk group) the annual risk of stroke is estimated at 1-1.5%. The moderate risk group (with 1 risk factor) has annual risk of stroke of 2.5-4%, while for the high risk group (more than 1 risk factor) it is 5-6%/year. Treatment with oral anticoagulants can diminish the risk of stroke by about 70%. Using only acetylsalicylic acid reduces the risk only by about 20%. We have to remember that patients with a history of stroke or TIA treated with aspirin only have a risk of further stroke of 10-12% per year and this group of patients could profit from oral anticoagulant treatment.